Shear strengthening of RC beams with NSM CFRP laminates : experimental research and analytical formulation - Dias, Salvador J. E. (2013)
The effectiveness of the NSM technique with CFRP laminates for the shear strengthening of RC beams with a certain percentage of steel stirrups was assessed by an extensive experimental research. In this context, the influence of the following parameters was investigated: concrete strength; percentage of existing steel stirrups; percentage and inclination of the CFRP laminates; existence of cracks when the RC beams are shear strengthened with NSM CFRP laminates. The results show that the higher is the concrete strength class the larger is the effectiveness of the NSM technique. The effectiveness of the CFRP laminates was higher in the beams with the lower percentage of steel stirrups. Inclined laminates were more effective than vertical laminates and the shear resistance of the beams has increased with the percentage of laminates. Pre-cracked RC beams shear strengthened with NSM CFRP laminates have presented a load carrying capacity similar to that of the homologous beams that were uncracked when strengthened. Taking the results obtained in the experimental research, an analytical formulation to predict the contribution of the possible distinct NSM shear strengthening configurations for the shear resistance of RC beams was developed. This analytical formulation is presented and its predictive performance is assessed. KEYWORDS: